Analysis of the Karl Heinrich Menges`S Concepts on Karakalpak Phonology - Awezova, Kamila (European Journal of Life Safety and Stability (2660-9630), 2023)
The Kazakh, Bashkir, Tatar, Kumyk, Kashay-Balkar, and Kyrgyz languages are all part of the Kipshak branch of the Karakalpak Turkic languages. Due to its close closeness to Uzbek, the grammar of the Karakalpak language has been greatly impacted by Uzbek. The Karakalpak language has grammatical characteristics, an agglutinative system, and other traits with numerous Turkic languages. Start-Object-File is the order. The Karakalpak language derives from the Altai language family and is a member of the Turkic language family. The language of the Karakalpak people also evolved together with it. The Nogayl Horde's dispersion in the 14th–16th century marked the emergence of the Karakalpak nation or the word Karakalpak.[1:73] In the Republic of Karakalpakistan, Uzbekistan, the Karakalpak language is spoken. The Karakalpak language is spoken by about 2,000 individuals in Afghanistan, Russia, Kazakhstan, Turkey, and other diasporas across the world.Back-East and North-West are the two dialects of the Karakalpak language that the ethnologist differentiates. In the province of Fergana, Menges tried to speak this dialect as much as they can. The East-West dialect uses the sounds /sh/ and /tch/. The appeal of the literary language has altered together with the emergence of the Karakalpak national tongue. The bulk of individuals utilize literary language in its charming version as their everyday speech. Two dialects make up the Speaking language, the primary variety of the Karakalpak language. The rear portions of our country had the latest dialectal distinctions, whereas the Turtkul, Elik kala, and Beruniy regions had the first. There are two dialectal variants that define the literary form of Karakalpak. The common Shagatai script used by the Central Asian peoples was the environment in which the Karakalpak script language first developed around the turn of the 20th century. But despite all the changes in the national language and the little contribution of the majority of Karakalpak people, this literary language is a stable literary language. The archaic literary script of the Karakalpak people's written language was used to learn this ancient language. Written literature spans a wide range of genres, including artistic, social-political, scientific-technical, journalistic, educational tools, etc. It was written in the language of literature.